PENGARUH UKURAN PERUSAHAAN, TIPE INDUSTRI, DAN KEBERAGAMAN GENDER DEWAN DIREKSI TERHADAP PENGUNGKAPAN EMISI KARBON - Meuthia Fakhira Irham (2021)
The study aims to analyze the effect of Firm Size, Industry Type and Gender Diversity of Board Directors. The population in this study are companies listed on the Indonesia Stock Exchange in the 2017-2019 period. A total of 58 samples are used per year. Firm Size is measured by natural logarithm of total asset, Industry Type is measured by dummy variable and Gender Diversity of Board Directors is measured by the Blau Heterogeneity Index. Carbon Emission Disclosure is measured using a carbon emission disclosure checklist. The method of analysis in this study uses descriptive analysis and multiple linear regression analysis hypotheses. The results of this study indicate that Industry Type have a positive and significant effect on Carbon Emission Disclosure. Firm Size and Gender Diversity of Board Directors has no significant effect on Carbon Emission Disclosure.